Composition and diversity of forest species in forests temperate of Puebla, Mexico - López Hernánez, Juan Antonio; Aguirre-Calderón, Óscar A.; Alanís-Rodríguez, Eduardo; Monarrez Gonzalez, José Carlos; González-Tagle, Marco A.; Jiménez-Pérez, Javier (Instituto de Ecología, A.C., 2017)
The objective of this research was to evaluate the composition and diversity of forest species in temperate forests in the eastern part of Puebla state, in central Mexico. A database was obtained from 45 permanent forestry research sites located in the Central and Pico de Orizaba forestry region, belonging to the Forest Management Unit, Umafor 2105. Dasometric information was recorded, including total height (m), diameter at breast height (cm) and crown cover of specimens with a diameter at height chest greater or equal to 7.5 cm. For each of the species, dominance was quantified through the basal area, and abundance calculated according to the number of trees and their frequency within the sample plots; a weighted value was generated for each species, known as the importance value index (IVI). Diversity and species richness were estimated using the Shannon-Wiener diversity (H ') and Margalef (DMG) indices. The results showed 11 tree species belonging to five genera. The richest family was Pinacea, with six species, of which P. montezumae presented the highest values of density, basal area and crown area, followed by A. religiosa. For the studied community, a Shannon-Wiener index value of 1.37 and a Margalef index (DMG) value of 1.35 were recorded. These values indicate a tendency towards heterogeneity in the ecosystem.